Human Capital Management and AI-Readiness in Islamic Religious Education: Toward an Islamically Grounded Competency Framework for PAI Teachers - Rizal Anshorudin; Dudu Rohman; Dede Supriyatna; Uus Ruswandi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid development of artificial intelligence (AI) in education has created an urgent need for all teachers including Islamic Religious Education (PAI) teachers to develop responsible AI competencies. Despite growing academic interest, a coherent and empirical evidence-based framework to address AI readiness for Pai teachers within the framework of Islamic values is still not available. This study systematically synthesizes evidence related to competency frameworks, professional development approaches, Islamic ethical foundations, and institutional conditions that support the responsible integration of AI by Pai teachers. The systematic literature review (SLR) was conducted in reference to the PRISMA 2020 protocol on five academic databases: Scopus, Web of Science, ERIC, and Google Scholar. After a gradual screening, 14 Indexed articles published between 2021 and 2026 were included in the thematic synthesis. Four thematic clusters were identified: AI teacher readiness and competence gaps, professional development and Strategic Human Resource Management, Islamic ethical framework for AI governance, and supportive institutional conditions. The findings reveal a structural asymmetry between teachers ' strong Islamic pedagogical foundations and AI's undeveloped technical competence. From this synthesis, the READIE Framework (Readiness, Ethics, and AI Development in Islamic Education) was developed, which consists of six interdependent dimensions, united by a core of Islamic Human Capital based on insan kamil, tawazun, and rahmatan lil 'alamin. The framework offers a theoretically coherent and institutionally applicable model for developing PAI teachers ready for the AI era.